Evaluasi Kinerja Ipal Produksi Industri Crumb Rubber (Studi Kasus: PT. X Kota Jambi) - Marhadi Marhadi; Hadrah Hadrah; Sri Wahyudi (Universitas Batanghari Jambi, 2022)
Wastewater treatment is the main element in the success of a business in environmental management and monitoring, for this reason it is necessary to carry out maintenance and evaluation so that the sustainability of environmental protection continues. The crude rubber industry (crumb rubber) generally processes rubber in several stages, starting from sorting raw materials, cleaning bokars, macro mixing, pre-drying, crushing, drying and pressing, of course, this produces waste. The research method is evaluating the quality of wastewater from each treatment unit at the WWTP production of crumb rubber, as well as evaluating the WWTP units based on design criteria that are planned and described analytic descriptively. upon admission, namely COD of 12.876 mg/L, TSS of 1.112 mg/L, BOD5 of 980 mg/L, Ammonia 2.3 mg/L, Nitrogen 96 mg/L, pH 6.3. The results at the outlet are COD 19.35 mg/L, TSS 58.67 mg/L, BOD5 35.1 mg/L, Ammonia 0.2 mg/L, Nitrogen 10 mg/L, pH 7. While the WWTP unit design inefficient in terms of design criteria, this is because the residence time is calculated too quickly, therefore it is necessary to analyze the suitability of dimensions in order to meet the required design criteria.